Direct Electrochemical Reduction of Natural Ilmenite into Ferrotitanium Alloys in a Molten Salt of LiCl-Li2O. Issue 2 (12th February 2021) - Yoo, BungUk; Ri, Vladislav; Kwon, SukCheol; Cho, SooHaeng; Nersisyan, Hayk. H.; Park, Kyoung-Tae; Lee, JongHyeon
Abstract : This paper reports a promising method to decrease the operating temperature during electrolysis of natural ilmenite to produce a porous and laminar flake-type intermetallic ferrotitanium (Fex Ti, x = 1, 2) with a thickness of less than 1 μ m by choosing a LiCl-Li2 O electrolyte with a lower operating temperature (625 °C) under an inert atmosphere. Results indicate that the Li2 O content in the electrolyte has a key effect on the phase transformation of natural ilmenite occurring in the electrochemical reduction process. Full conversion of natural ilmenite into ferrotitanium products can be achieved when the Li2 O amount in the electrolyte and the cell voltage are approximately 1 wt.% and −2.5 V, respectively. In addition, the electrochemical reduction mechanism of natural ilmenite is proposed and discussed based on our experimental results and thermodynamic analysis.